CHARACTERISTICS OF ANEMIA IN CHILDREN WITH HIV INFECTION - Ghozali, Mohammad; Adhi Sunjaya, Al Farizi; Indrati, Agnes Rengga (Faculty of Medicine, Universitas Padjadjaran, 2018)
Anemia is a hematologic complication commonly encountered in HIV patients. Although the severity of anemia is generally mild, anemia has been shown to be a strong risk factor for disease progression, particularly in HIV infected person. With different severity and types of anemia in HIV patients, it is necessary to identify the severity and type of anemia in HIV-infected children, thus helping to determine the prognosis and management of their anemia. The purpose of this study was to describe HIV patient staging infection, co-morbidities, and type of anemia in HIV-infected children based on their therapy. A descriptive quantitative research was conducted in Dr. Hasan Sadikin General Hospital Bandung. Data were collected from patients? medical records diagnosed with HIV between 2015?2017. The severity of anemia was set according to World Health Organization standards in 2011 and the types of anemia were identified from the erythrocyte index on routine hematologic examination. Forty-seven of 73 children had anemia. Based on the severity of anemia, 26% mild anemia, 60% moderate anemia, and 15% severe anemia were found. Subsequently, hypochromic microcytic (40%), macrocytic (32%), and normocytic normochromic (28%) anemia were identified. Considering the direct and indirect mechanism to yield anemia in HIV-infected patients, this double sword symptom becomes the most common complication burdened the growth and development of HIV-infected children. This study made it even more pronounced. Key words: Anemia, Children, HIV Karakteristik Anemia pada Anak Terinfeksi HIVAnemia adalah komplikasi hematologi paling sering ditemukan pada pasien HIV. Meskipun tingkat anemia pada umumnya ringan, anemia telah terbukti menjadi faktor risiko kuat terhadap perkembangan penyakit. Terdapat perbedaan tipe anemia pada pasien HIV dengan etiologi yang berbeda pula sehingga perlu dilakukan identifikasi mengenai tingkat dan tipe anemia pada pasien HIV anak, yang pada akhirnya dapat membantu menentukan prognosis dan penatalaksanaan anemia pada pasien ini. Suatu penelitian deskriptif kuantitatif ini bertujuan mengetahuitingkat dan tipe anemia dengan mengklasifikasikannya berdasarkan komorbiditas pada pasien HIV/AIDS anak di RSHS tahun 2015?2017 menggunakan data rekam medik pasien pemeriksaan hematologi rutin. Tingkat anemia ditetapkan berdasar atas standar WHO, sementara jenis anemia dilihat dari indeks eritrosit. Sebanyak 73 pasien anak terinfeksi HIV, didapatkan 47 anak mengalami anemia. Tingkat anemia ditemukan anemia ringan (26%), anemia sedang (60%), dan anemia berat (15%). Tipe anemia yang ditemukan adalah normositik normokromik (28%), makrositik (32%), dan mikrositik hipokromik (40%). Tingkat anemia pada pasien HIV anak di RSHS pada umumnya adalah anemia sedang. Tipe anemia terbanyak pada penelitian adalah mikrositik hipokromik. Kata kunci: Anak, anemia, HIV